Penjatuhan Pidana Khusus Perkara Narkotika Atas Penerapan Asas the Binding Persuasive of Precedent - OKTAFIANTO, SETIYA BUDI; SUGIYARTO, SUGIYARTO; SETYAWAN, ANDHI; NUGROHO, AGUNG BUDI; PUTRA, TEGAR HARBRIYANA (Universitas Muhammadiyah Metro, 2025)
Narcotics crime is one of the special crimes which is also specifically regulated through Law Number 35 of 2009 concerning Narcotics, in other words it is regulated outside the Criminal Code. In deciding a narcotics crime, the judge will consider certain matters in accordance with the relevant law and make a decision in accordance with his belief in upholding a just law. The type of research used is normative legal research. The most relevant approach is the case approach by examining cases of court decisions that also have permanent legal force (inkraht). The sources of legal materials are primary legal materials and secondary legal materials using library research collection techniques, as well as analytical techniques in this legal research which are deductive in nature using the syllogistic method. The results of the study show that the judge's consideration in imposing a sentence below the special minimum can use several benchmarks such as looking at the age of the defendant who is underage or elderly, the involvement of the defendant in a narcotics crime, the weight of narcotics evidence obtained from the defendant, and the possibility of the defendant repeating the crime. The legal consequence of imposing sanctions below the specific minimum on the application of the binding persuasive of precedent principle is related to aspects of justice, namely that it will open up the possibility of causing criminal disparities which in the end the convict will feel injustice and become a victim of discrimination in law enforcement.